January and July regional climate simulation over South America - Nicolini, M. (2002)
[i] This work presents results, over the South American region, from the CSIRO Division of Atmospheric Research limited area model (DARLAM) and from the ninelevel general circulation model (GCM) of CSIRO (CSIRO Mk 2), within which it was nested in a one-way mode. Ten separate 30-day DARLAM simulations were performed for both January and July with a resolution of 125 km and were averaged to obtain a climatology for those months. This paper presents for the first time simulations of the January South American climate using a limited area model; previous similar studies simulated only the July climate. The goal of this study was to examine the capability of the CSIRO Mk 2 - DARLAM nested modeling system for simulating the climate in the South American region. Further, it was desired to investigate whether the higher resolution of DARLAM improves the simulated climate over various subregions, compared with the GCM and observations. With this purpose, a representative set of variables was analyzed and statistically compared. Overall, the fields simulated by the nesting system provide a better representation of the South American climate than the GCM. In particular, significant improvements are found in the nested model climatology for near-surface temperature and mean sea level pressure. Comparison of the January and July simulations shows a better wintertime performance. Some significant summertime features, like the Bolivian High, are reasonably well simulated by DARLAM, but not by the GCM. Copyright 2002 by the American Geophysical Union.